Reducing Depression with Classical Music Therapy in Chronic Kidney Failure Patients Undergoing Hemodialysis - Vivi Sovianti; Emilia Puspitasari; Gianinda Wening Saraswanty; Maya Cobalt Angio S; Siti Juwariyah; Miss Nafisah (SABDA EDU PRESS (SEP), 2024)
Background: Chronic Kidney Failure problems during hemodialysis may include depression. Depression refers to the mental, thought, feeling, and behavioral problems of patients. The causes of depression include genetics, physical disease, lifestyle, and drugs. One of the therapies to relieve depression is music therapy. This research determines the influence of music therapy to relieve the depression levels of chronic kidney failure patients with hemodialysis. The applied method was quantitative with a quasi-experimental design and one group pretest-posttest. The samples consisted of 45 respondents taken by accidental sampling. The applied instruments were BDI and the music therapy SOP. All instruments were examined in terms of validity, reliability, and expert judgment. The statistic test applied a non-parametric Wilcoxon test. The results showed the influence of classical music therapy and the relieved depression levels of chronic kidney failure patients with hemodialysis. The obtained p-value is 0.000, lower than 0.05. The researcher concluded the implementation of classical music was effective to relieve the depression symptoms of chronic kidney failure patients with hemodialysis. The researcher suggests developing a combined classical music therapy to relieve depression in chronic kidney failure patients. The researcher suggests the implementation of intervention and control groups to compare the significance of the results.